Carbon nanotubes as excitonic insulators - Daniele Varsano (Nature Portfolio, 2017)
It has long been anticipated theoretically that semiconductors with small band gaps may form a correlated exciton insulator phase, but it has been difficult to find material realisations. Here, the authors predict numerically that zero-gap armchair carbon nanotubes could be exciton insulators.